The Effect of Infusion of Basil Leaves (Ocimum Basilicum L) on Pathological Flour Albus in Women of Childbearing Age - Sulistiyowati, Sulistiyowati; Irawan, Dwi Dianita; Sari, Ponco Indah Arista (Universitas Islam Lamongan, 2022)
Flour albus is one of three women's problems that were originally considered a common problem but eventually become severe and even cause infection. The problem of this research was the high incidence of pathological flour albus. The purpose of this study was to determine the difference in pathological flour albus before and after administration of basil leaf infusion (in women of childbearing age (WUS) at Independent Midwifery Practice Ny. Aida Hartatik, S.ST Dlanggu-Deket-Lamongan. This research applied pre-experimental research design with one-group pre-test-post-test-design approach. The population was all women of childbearing age who experienced flour albus at BPM Ny. Aida Hartatik, S.ST in February-June 2019. The samples were twenty-five women obtained by incidental sampling. The research variables were pathological flour albus and treatment with basil leaf infusion. The data were taken by interview and observation. Then, the data were analyzed by Wilcoxon Signed Rank statistical test with a significant level of = 0.05. The results showed that 64% of women of childbearing age before being given basil leaves increased while 72% of women of childbearing age after being given basil leaf infusion decreased. There were differences in pathological flour albus before and after infusion of basil leaves in women of childbearing age with Z=-2,800 and p=0,000. In addition to being given basil leaf infusion (Ocimum Sanctum L), another effort to overcome this problem is through the participation of health workers in providing early information about the prevention and treatment of pathological flour albus.